2005
DOI: 10.1128/mcb.25.10.3906-3913.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by Cak1 Regulates the C-Terminal Domain Kinase Ctk1 in Saccharomyces cerevisiae

Abstract: Ctk1 is a Saccharomyces cerevisiae cyclin-dependent protein kinase (CDK) that assembles with Ctk2 and Ctk3 to form an active protein kinase complex, CTDK-I. CTDK-I phosphorylates Ser2 within the RNA polymerase II C-terminal domain, an activity that is required for efficient transcriptional elongation and 3 RNA processing. Ctk1 contains a conserved T loop, which undergoes activating phosphorylation in other CDKs. We show that Ctk1 is phosphorylated on Thr-338 within the T loop. Mutation of this residue abolishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…CDC28-dependent bypass of cak1 phenotypes but not ctf7 phenotypes: Cak1p phosphorylates many substrates including Kin28p, Bur1p, and Ctk1p, but the only essential role for Cak1p kinase is to activate Cdc28p (Espinoza et al 1996(Espinoza et al , 1998Cross and Levine 1998;Yao and Prelich 2002;Ostapenko and Solomon 2005;Ganem et al 2006). If the synthetic lethality that we observed between ctf7 and cak1 was in fact due to diminished CDK activation, we reasoned that Cak1p-bypass CDC28 alleles (Cross and Levine 1998) should rescue both cak1-277 temperature sensitivity and ctf7 cak1 synthetic lethality.…”
Section: Resultsmentioning
confidence: 99%
“…CDC28-dependent bypass of cak1 phenotypes but not ctf7 phenotypes: Cak1p phosphorylates many substrates including Kin28p, Bur1p, and Ctk1p, but the only essential role for Cak1p kinase is to activate Cdc28p (Espinoza et al 1996(Espinoza et al , 1998Cross and Levine 1998;Yao and Prelich 2002;Ostapenko and Solomon 2005;Ganem et al 2006). If the synthetic lethality that we observed between ctf7 and cak1 was in fact due to diminished CDK activation, we reasoned that Cak1p-bypass CDC28 alleles (Cross and Levine 1998) should rescue both cak1-277 temperature sensitivity and ctf7 cak1 synthetic lethality.…”
Section: Resultsmentioning
confidence: 99%
“…Hypomorphic mutations of the essential CAK1 or MPS1 genes produce spore wall defects similar to those seen in smk1 mutants, although unlike Smk1p, both of these kinases have distinct functions earlier in sporulation (19,148,150,161,177). In vegetative cells, CAK1 is required for phosphorylation of Cdc28p and other cyclin-dependent kinases on a threonine in an analogous position to the activating phosphorylation sites in Smk1p (37,69,117,184). Smk1p is not phosphorylated in a cak1 hypomorphic mutant (148).…”
Section: Vol 69 2005 Ascospore Formation In Saccharomyces Cerevisiamentioning
confidence: 99%
“…Thus, previous studies demonstrated that Cak1 phosphorylates Kin28, Bur1, and Ctk1 within their T loops and stimulates their activities (22,36,52,72). Therefore, we tested whether Cak1 levels were altered in the absence of SUB1.…”
Section: (D)mentioning
confidence: 99%